1992
DOI: 10.1212/wnl.42.6.1209
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain and muscle energy metabolism shown by 31 P magnetic resonance spectroscopy in patients affected by migraine with aura

Abstract: We studied brain and muscle energy metabolism by phosphorus 31 magnetic resonance spectroscopy (31P-MRS) in 12 patients affected by migraine with aura (classic migraine) in interictal periods. Brain 31P-MRS disclosed a low phosphocreatine content in all patients, accompanied by high adenosine diphosphate concentration, a high percentage of V/Vmax (adenosine triphosphate), and a low phosphorylation potential--features showing an unstable state of metabolism in classic migraine. Abnormal muscle mitochondrial fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
127
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(138 citation statements)
references
References 0 publications
10
127
1
Order By: Relevance
“…Our present findings confirm and extend previous results reported by Eleff et al (1990) and our group (Montagna et al, 1992) that impaired mitochondrial function of brain cortex may be associated with any of the clinical expressions of mitochondrial cytop athies, and that 31p MRS is able to uncover a deficit of brain energy metabolism not only in affected pa tients, but also in those patients without any brain symptoms and/or signs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present findings confirm and extend previous results reported by Eleff et al (1990) and our group (Montagna et al, 1992) that impaired mitochondrial function of brain cortex may be associated with any of the clinical expressions of mitochondrial cytop athies, and that 31p MRS is able to uncover a deficit of brain energy metabolism not only in affected pa tients, but also in those patients without any brain symptoms and/or signs.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphorus magnetic resonance spectroscopy 31p MR spectra were acquired by a GE 1.5 T Signa system with a spectroscopy accessory using a surface coil provided by General Electric (Milwaukee, WI, U.S.A.) as recently reported (Barbiroli et al, 1992). The pulse width and transmitter power were adjusted to obtain max imal signal intensity.…”
mentioning
confidence: 99%
“…One study, Boska et al, reported only a depletion of PCr in anterior brain regions of MwA and the occipital cortex of FHM patients (11). The calculated value of the phosphorylation potential was significantly decreased in migraine patients, as reported in a number of studies (8,9,(12)(13)(14)(15) hence has a lower energy reserve, was also frequently observed (8,9,(13)(14)(15)18). The percentage of v/v max was found to be significantly increased in migraine patients (8,9,14,15).…”
mentioning
confidence: 78%
“…pH i was measured in all abovementioned studies and no significant pH i -changes were observed in all but three studies (13,14,18). The pH i -changes found in these studies should be regarded carefully, though, because of the presence of large standard deviations (13), borderline significance (14) or migrainous stroke (18).…”
mentioning
confidence: 90%
“…74,75 Reduced PCr concentrations have also been reported in migraine, which has been postulated to be associated with abnormal mitochondrial function. 76,77 Several 31 P MRS studies have suggested a connection between decreased levels of PCr and bipolar disorder (Table 5). A study by Kato et al 78 of bipolar patients across the full range of mood states (depressed, manic, and euthymic) observed significantly 22 Consequently, it is possible that the decreased PCr levels observed in these studies were due to the pharmacological effects of these treatments.…”
Section: Elevated Lactate In Bipolar Disordermentioning
confidence: 99%